End user satisfaction of e-BRIM application among Segamat citizen: an empirical study / Mohd Muzamir Ghazali...[et al.] - Ghazali, Mohd Muzamir; Ahmad, Nur Atiqah; Ahmad Zamzury, Nur Farhana; Tajuddin, Nur Shawani (2014)
User satisfaction is considered one of the most important measures of information systems success the end-user computing satisfaction . Other than that end user satisfaction with an information system as the overall affective evaluation an end-user has regarding on experience related with the information system. The end-user computing satisfaction instrument that developed by Doll and Torkzadeh in 1988 was used widely and also develop and validated an end user computing satisfaction (EUCS) instrument. It is included of five components as content, accuracy, format, ease of use and timeliness. This study is conducted to identify the satisfactory among user towards the use of e-BRIM application among Segamat citizen and also to investigate the elements that contribute to the user satisfaction. To measure the end-user satisfaction, the researcher also added the one element such as privacy. Moreover, this study also was conducted among the user in the Segamat citizen to examine the user satisfaction.